2010
DOI: 10.2478/s11756-010-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic adaptation in lichen phyco- and photobionts

Abstract: The effect of light quality on the photosynthetic pigments as chromatic adaptation in 8 species of lichens were examined. The chlorophylls, carotenoids in 5 species with green algae as phycobionts (Cladonia mitis, Hypogymnia physodes, H. tubulosa var. tubulosa and subtilis, Flavoparmelia caperata, Xanthoria parietina) and the chlorophyll a, carotenoids and phycobiliprotein pigments in 3 species with cyanobacteria as photobionts (Peltigera canina, P. polydactyla, P. rufescens) were determined. The total content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Two years later, Ballesteros et al (2006) found this species in cuticule of dead crayfish Austropotamobius pallipes in Spain and Kiziewicz et al (2013) observed its occurrence in water from the some springs of north-eastern Poland. Growth of A. frigidophilus was also stated on eggs of some species from Salmo genus (Czeczuga et al, 2004(Czeczuga et al, , 2011a, sturgeonids, Chinook salmon (Czeczuga et al, 2011b) and African catfish (Czeczuga et al, 2013). As shown in Table 3, such species as: A. irregularis, A. laevis, A. parasiticus and A. stellatus were found on plant debris and on fish eggs.…”
Section: Discussionmentioning
confidence: 83%
“…Two years later, Ballesteros et al (2006) found this species in cuticule of dead crayfish Austropotamobius pallipes in Spain and Kiziewicz et al (2013) observed its occurrence in water from the some springs of north-eastern Poland. Growth of A. frigidophilus was also stated on eggs of some species from Salmo genus (Czeczuga et al, 2004(Czeczuga et al, , 2011a, sturgeonids, Chinook salmon (Czeczuga et al, 2011b) and African catfish (Czeczuga et al, 2013). As shown in Table 3, such species as: A. irregularis, A. laevis, A. parasiticus and A. stellatus were found on plant debris and on fish eggs.…”
Section: Discussionmentioning
confidence: 83%
“…Aphanomyces frigidophilus was described as occurring on the eggs of the Japanese char Salvelinus leucomaenis and, for the first time in Europe, on the eggs of Coregonus lavaretus (Czeczuga et al, 2004). Aphanomyces frigidophilus also grows on some species from the Salmo genus (Czeczuga et al, 2011a), including sturgeonid fishes (Czeczuga et al, 2012b), Chinook salmon (Czeczuga et al, 2012a) and African catfish (Czeczuga et al, 2013), and on the alevins of the Nile tilapia (Czeczuga et al, 2014b), and on the eggs of Stenodus species (Czeczuga et al, 2014a). The immune response of rainbow trout to Aphanomyces invadans has also been examined (Thompson et al, 1999), and according to Khan et al (1998) and Oidtmann et al (2008), the rainbow trout is moderately susceptible to Aphanomyces invadans through intramuscular infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen carotenoids, such as -carotene, -carotene, -cryptoxanthin, lutein, zeaxanthin, canthaxanthin, astaxanthin, violaxanthin and neoxanthin ( Figure 10) were separated and identified (Czeczuga et al, 2010). Stereoisomers and epoxy/carbonyl derivatives ofcarotene were separated through Al 2 O 3 CC developed with 10-60% diethyl ether in n-hexane (Marty and Berset, 1990).…”
Section: Secondary Metabolites 145mentioning
confidence: 99%